2007
DOI: 10.1039/b700505a
|View full text |Cite
|
Sign up to set email alerts
|

Observation of intermediate-range order in a nominally amorphous molecular semiconductor film

Abstract: Synchrotron X-ray diffraction from a nominally amorphous molecular semiconductor film reveals both the presence of intermediate-range order (IRO) corresponding to crystalline domains with an average size of a few nanometres, and the growth of these domains upon exposure of the film to moisture.Due to a high demand for better, more efficient, and less expensive displays and lighting, the science and engineering community has concentrated efforts on the development, understanding and optimization of new electrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…In that study, it was established that a spin-coated fi lm did indeed consist of nanoscale crystalline domains. [ 52 ] Therefore, it is possible that complexes 1 -4 crystallize in different nanosized domains when spin-coated fi lms are prepared, and this may affect the movement of the counter-anions in the device and thereby the turn-on-time.…”
Section: Full Papermentioning
confidence: 99%
“…In that study, it was established that a spin-coated fi lm did indeed consist of nanoscale crystalline domains. [ 52 ] Therefore, it is possible that complexes 1 -4 crystallize in different nanosized domains when spin-coated fi lms are prepared, and this may affect the movement of the counter-anions in the device and thereby the turn-on-time.…”
Section: Full Papermentioning
confidence: 99%
“…It was reported that nanoscale crystalline domains are formed when spincoating concentrated films of iTMCs. [25] To speed up the occurrence of the electroluminescence, small amounts of ionic liquid (IL) can be added to the active layer [26] or short high-voltage pulses can be applied. [27] A rapid turn-on of the luminescence is achieved when a combination of these techniques is used (Fig.…”
Section: (Bpy)]mentioning
confidence: 99%
“…Assuming that as in films of [Ru(bpy) 3 ] 2þ nanoscale crystalline domains are also present in the solid films of these Ir-iTMCs, information about the origin of this low ionic mobility can be obtained from the crystal structure. [32] From the crystal structure ( Fig. 1) it can be observed that PF 6 À is enclosed between six iridium cations, which might be the reason for the low mobility of these anions.…”
Section: Electroluminescent Devicesmentioning
confidence: 99%